PENGARUH MEDIA SEMPOA TERHADAP KEMAMPUAN DASAR PERKALIAN DENGAN TEKNIK PENJUMLAHAN BERULANG PADA SISWA KELAS II SDN 1 NOYAN - Adam, Fransisco; Riyanti, Vera; Libertus, Libertus (Jurnal Pembelajaran Prospektif, 2025)
Students' ability to understand math is still very low, especially the basic ability of multiplication, the students cannot solve math problems well so that it affects their learning outcomes. The purpose of this study was to determine the effect of using abacus media on basic multiplication skills with repeated addition techniques in grade II students of SDN 1 Noyan. The research method is experimental with one group pretest-posttest design. The instruments used were tests and observation sheets. The statistical test results showed there was a significant difference between the pretest and posttest scores Thitung = 3.50 > Ttabel = 1.729, which means the use of abacus media has a positive effect on student learning outcomes in basic multiplication material. The results of this study indicate that concrete media such as an abacus can improve students' understanding of basic math concepts.